2023
DOI: 10.1186/s12909-023-04250-z
|View full text |Cite
|
Sign up to set email alerts
|

Are early career family physicians prepared for practice in Canada? A qualitative study

Abstract: Background In Canada, the College of Family Physicians of Canada (CFPC) introduced Competency Based Medical Education to prepare and train family medicine residents to be competent to enter and adapt to the independent practice of comprehensive family medicine. Despite its implementation, the scope of practice is narrowing. This study aims to understand the degree to which early career Family Physicians (FPs) are prepared for independent practice. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Across multiple domainssuch as primary care, emergency care, hospital inpatient care, advocacy, and scholarship-early career family physicians have indicated that their training prepares them for some professional activities but not others. 9 Ongoing results of the CFPC FMLS show that the most second-year family medicine residents believe they have had good exposure in areas like mental health, chronic disease management, and providing care across the life cycle. However, many have identified limited exposure to intrapartum care (16%), palliative care (17%), office-based clinical procedures (19%), practice in long-term care homes (38%), in-hospital clinical procedures (58%), and care for Indigenous populations (38%).…”
Section: Response To Lavergne Et Almentioning
confidence: 99%
“…Across multiple domainssuch as primary care, emergency care, hospital inpatient care, advocacy, and scholarship-early career family physicians have indicated that their training prepares them for some professional activities but not others. 9 Ongoing results of the CFPC FMLS show that the most second-year family medicine residents believe they have had good exposure in areas like mental health, chronic disease management, and providing care across the life cycle. However, many have identified limited exposure to intrapartum care (16%), palliative care (17%), office-based clinical procedures (19%), practice in long-term care homes (38%), in-hospital clinical procedures (58%), and care for Indigenous populations (38%).…”
Section: Response To Lavergne Et Almentioning
confidence: 99%